SEMANTIC ANALYSIS OF PHRASEOLOGAL UNITS WITH RHE COMPONENT OF "FAUNA" - Daminov Jakhongir Alisherovich (Journal of new century innovations, 2024)
Abstract: In this article, phraseologisms involving lexemes with animal archisemes are analyzed from semantic point of view. It also refers to the writer's style and use of words.